Manajemen Funderaishing Wakaf Tunai Di Lembaga Lelang Sertifikat Wakaf - Abd. Wafi (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Discussions on waqf have generally focused on fixed assets such as mosques, land, buildings, schools, and Islamic boarding schools. However, the increasing need for cash funds in modern society to improve economic welfare has encouraged the emergence of innovations in the form of cash waqf. One of the efforts to manage cash waqf is through fundraising activities, which involve collecting funds from individuals, organizations, and legal entities. This study aims to analyze the fundraising strategy of waqf as a source of funding for the construction of the Al-Ittihad Madrasah building through a waqf certificate auction mechanism. This research uses a qualitative method with a descriptive-analytical approach. The data are presented in the form of written descriptions rather than numerical or statistical data, explaining phenomena based on the data obtained from the research findings. Data collection techniques include observation, interviews, and documentation.The results of the study show that the management of cash waqf fundraising through a waqf certificate auction institution has its own characteristics, including the waqf management system, fundraising management strategies, and the utilization of digital media in the modern era to reach a wider community. In addition, the program has received positive responses from the community and local leaders. The existence of this waqf certificate auction institution also provides a solution for the community to participate in development while making it easier to engage in charitable investment for the hereafter.